PENGARUH TIME DEMANDS OF WORK TERHADAP KEPUASAN KERJA, STRESS KERJA, DAN TURNOVER INTENTION KARYAWAN (Studi Pada Karyawan PT. Bank Tabungan Negara (Persero) Tbk. Cabang Harapan Indah, Bekasi) - Hasanah, Anisah Uswatun; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2016)
The aim of this research is to analyze the impact time demands of work, on job satisfaction, job stress, and employee turnover intention PT. Bank Tabungan Negara (Persero) Tbk. Cabang Harapan Indah, Bekasi               This study is using path analysis with SmartPLS 2.0.M3. The population that used in the study is all the employees of PT. Bank Tabungan Negara (Persero) Tbk. Cabang Harapan Indah, Bekasi, which are 108 respondents. The amount of the sample is determined by the census method of the entire employee. However the sample that has been applied into 85 respondents significantly decreased into 85people.            The results have shown that the time demands of work do not significantly influence turnover intention. Furthermore the time demands of work have no significant effect on job satisfaction. Employee satisfaction negatively affect on turnover intention. Job satisfaction is not successfully mediating the relationship between the time demands of work and turnover intention. Time demands of work have positive influence on job stress. Job stress has positive effect on turnover intention. Job stress has been successfully mediating the relationship between the time demands of work and turnover intention. Job stress negatively affect with job satisfaction. Job satisfaction also has been successfully mediating the relationship between job stress and turnover intention.